SCHOOL MANAGEMENT IN INCREASING THE QUALITY OF EDUCATION AT BANYUAJUH 6 ELEMENTARY SCHOOL - Wahyu Triandani; Agung Setyawan (Citra Dharma Cindekia, 2022)
The success of the quality of education is largely determined by the leadership of the principal in managing teachers, facilities and infrastructure, and students. The teacher as the central figure in the class needs special attention and special treatment so that the teacher can maximize his role. Likewise with the management of school facilities and infrastructure and students. The use of facilities and infrastructure as a tool to support the success of education needs to get good management. The purpose of this study was to analyze school management to improve the quality of education at Banyuajuh 6 Elementary School. The method used in this study was descriptive qualitative with data collection techniques in the form of interviews, observation and documentation. The results of the study stated that in the implementation of the Banyuajuh 6 Elementary School management program, the strategy applied was to achieve an increase in the quality of education, including: program socialization, SWOT analysis, problem solving, quality improvement, and monitoring and evaluation of school program implementation.